A managerial perspective on factors leading to failure in information technology projects - Ghebre-egziabiher, Tesfagabir Ghebreyohannes (University of the Free State, 2005)
This research is based on data collected between April and May 2004 from 150 sample companies registered at the Johannesburg Stock Exchange. The study was organised into six chapters. The first chapter presents the research design, a framework that guides the research from beginning to end. Chapter two presents the theoretical background of project management. Then follows the secondary data findings about IT projects and the factors that lead to failure in IT projects. Chapter four presents the research design and methodology follow this. In the fourth chapter design issues such as data collection techniques, sample design and research instruments implemented are described. Following this primary data analysis is presented. Finally the study ends with the presentation of findings, a conclusion and recommendations. The research results show that - the overall IT project performance has improved to higher degree than was previously reported - a high number of projects still exceed the budget, fall behind schedule and fail to provide the expected benefit - on average, 25 % of IT project work requires reworking - human resource related (people related) problems are the first predictors of the overall IT project failure, followed by project management related problems - the project managers lack the soft and managerial skills necessary for managing IT projects - despite their positive view of project management tools and techniques, the project managers hardly use the project management tools and techniques in practice. - There was no statistically significant performance difference between in-house and out sourced projects. - Poor planning and poor business case were the foremost predictors of failure according to the ranking of the project managers. And the most important recommendations are: - The alignment of IT project goals with overall business strategy and goals, - having a good start backed by the clear definition of requirements and clear project definition, - ensure a general consensus is reached on project success criteria, - manage risk continuously, - end-users should be involved for greater success, - a sound project management methodology should be applied at all times, - project managers should be developed and empowered to implement the project management methodology.

Hierdie navorsing is gegrond op gegewens wat tussen April en Mei 2004 ingesamel is van 150 steekproefmaatskappye wat op die Johannesburgse Aandelebeurs (JSE) geregistreer is. Die studie is in ses hoofstukke ingedeel. Die eerste hoofstuk verteenwoordig die navorsingsontwerp, ‘n raamwerk wat van begin tot einde ‘n rigsnoer vir die navorsing is. Hoofstuk twee verteenwoordig die teoretiese agtergrond van projekbestuur. Daarna volg die sekondêre bevindings van die gegewens oor IT-projekte en die faktore wat aanleiding gee tot mislukkings in IT-projekte. Hoofstuk vier verteenwoordig die navorsingsontwerp en metodologie volg hierop. In die vierde hoofstuk word sake met betrekking tot ontwerp soos tegnieke vir die insameling van gegewens, steekproefontwerp en navorsingshulpmiddels wat gebruik word, beskryf. Hierna word primêre data-ontleding aangebied. Laastens eindig die studie met die aanbieding van bevindings, ‘n gevolgtrekking en aanbevelings. Die navorsingsresultate toon dat - die algehele prestasie van IT-projekte het tot ‘n groter mate verbeter as wat voorheen gerapporteer is - ‘n groot aantal projekte oorskry steeds die begroting, raak agter by die skedule en slaag nie daarin om die verwagte voordeel te verskaf nie - gemiddeld 25% van werk aan IT-projekte moet oorgedoen word - probleme met betrekking tot menslike hulpbronne (dit wil sê wat verband hou met mense) is die eerste voorspellers van die algehele mislukking van IT-projekte, gevolg deur probleme wat verband hou met projekbestuur - dit ontbreek die projekbestuurders aan die sagte en bestuursvaardighede wat nodig is vir die bestuur van IT-projekte - ten spyte van hulle positiewe siening van die hulpmiddels en tegnieke van projekbestuur, benut projekbestuurders nouliks die hulpmiddels en tegnieke van projekbestuur in die praktyk. - Daar was statisties geen noemenswaardige prestasieverskille tussen interne en uitgekontrakteerde projekte nie. - Swak beplanning en ‘n swak besigheidsaak was die belangrikste voorspellers van mislukking volgens die ranglys van die projekbestuurders. En die belangrikste aanbevelings is: - Die in lyn bring van IT-projekdoelwitte met die algehele besigheidstrategie en doelwitte, - om ‘n goeie begin te hê, gerugsteun deur die duidelike omskrywing van vereistes en van die projek, - verseker dat algemene konsensus bereik is oor die kriteria vir die sukses van die projek, - risiko moet op ‘n gereelde grondslag bestuur word, - eindgebruikers moet betrek word om groter sukses te behaal, - ‘n gesonde metodologie vir die bestuur van die projek moet te alle tye toegepas word, - projekbestuurders behoort ontwikkel en bemagtig te word om die metodologie van die projekbestuur toe te pas
Dissertation (M.Com. (Business Management))--University of the Free State, 2005
Keywords: Project management; Project management tools and instruments; IT projects; Business management; IT project management; IT project failure; Managing through projects; Project lifecycles; Project management capability; Project team; Project learning; Project organisational structure; Success in business; Information technology -- Management